2000
DOI: 10.1086/315916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Deficiency on Th1 and Th2 Cytokine Shifts

Abstract: Nutritional deficiency of zinc is widespread throughout developing countries, and zinc-deficient persons have increased susceptibility to a variety of pathogens. Zinc deficiency in an experimental human model caused an imbalance between Th1 and Th2 functions. Production of interferon-gamma and interleukin (IL)-2 (products of Th1) were decreased, whereas production of IL-4, IL-6, and IL-10 (products of Th2) were not affected during zinc deficiency. Zinc deficiency decreased natural killer cell lytic activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
257
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(271 citation statements)
references
References 36 publications
7
257
1
6
Order By: Relevance
“…Zn is an important micronutrient in the body with numerous functions, including growth, nerve impulse transmission, hormone release, and activation of immune-enhancing T-cells [12] . In an experimental study, Prasad et al [13] stated that a significant decrease in Zn concentrations was associated with a decrease in interferon-gamma and interleukin (IL)-2 production as well as the nat- [9] demonstrated that patients with sepsis had significantly lower plasma Zn concentrations compared to control subjects. Consistent with our results, Elemraid et al [11] also reported significantly reduced serum Zn levels in patients with chronic suppurative otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…Zn is an important micronutrient in the body with numerous functions, including growth, nerve impulse transmission, hormone release, and activation of immune-enhancing T-cells [12] . In an experimental study, Prasad et al [13] stated that a significant decrease in Zn concentrations was associated with a decrease in interferon-gamma and interleukin (IL)-2 production as well as the nat- [9] demonstrated that patients with sepsis had significantly lower plasma Zn concentrations compared to control subjects. Consistent with our results, Elemraid et al [11] also reported significantly reduced serum Zn levels in patients with chronic suppurative otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of healthy lifespan and longevity, nutrigenetic and nutrigenomic implications around this last nutrient (zinc) appear very important taking into account that: (1) RDA (11 mg/day for men and 8 mg/day for women) and UL (40 mg/day for adults) for zinc are very close [50]; (2) About 10% of the human proteome consists in potential Znbinding proteins [5]; (3) Proteins devoted to Zn transport (ZnT) and buffering, most of which display functional polymorphic sites, include at least ten members of the ZnT family [134], 15 members of the ZIP family (i.e. Zn-regulated metal transporter, iron-regulated metal transporterlike protein) [36,134] and ten distinct isoforms of MT [150]; 4) zinc is an essential micronutrient strictly involved in regulating gene expression [35], inflammatory response [63,124] and antioxidant activity [125].…”
Section: Human Genes and Longevitymentioning
confidence: 99%
“…A lot of evidences support the belief that the main factor associated with zinc deficiency seems to be an inadequate zinc dietary intake influenced in turn by other several intrinsic and extrinsic factors (Gibson et al 2008). Indeed, zinc is well recognised as an essential trace element for all organisms and plays an important role in the development and integrity of the immune system affecting both innate (T, NK, and NKT cells) and adaptive (anti/pro-inflammatory cytokine production) immune responses (Prasad 2000;Ibs et al 2003;Bogden 2004;Haase et al 2006b;Mocchegiani et al 2009). Zinc is required for DNA synthesis, RNA transcription, cell division and activation (Prasad 2007) as well as in preventing apoptosis (Fraker 2005).…”
Section: Introductionmentioning
confidence: 99%